Investigation of decision making styles of Turkish football coaches association administrators with respect to some parameters - (:unkn) unknown (My University, 2013)
The purpose of this study was to explore decision making styles of Turkish Football Coaches Association (TUFAD) administrators with respect to some parameters. Thus, Melbourne Decision-making Scale adapted to Turkish by Deniz [1] was applied to a sample of 55 administrators consisting of TUFAD president, board members and coaches who voluntarily participated in the study. The data obtained indicated no statistically significant relationship between decision-making styles with respect to the variables of age and educational background. It was explored that married participants had higher levels of self-confidence and lower levels of suspensive decision, and those who work as presidents demonstrated higher levels of careful decision. It was also found that coaches of youth development tended to have less avoidant and suspensive decision-making styles when compared to the coaches of amateur and professional teams. As a result, success depends largely on the right and healthy decisions of administrators when TUFAD administrators who are highly influential in Turkish football are fulfilling their missions and responsibilities. Right and appropriate decisions will have important effects on the success of sports associations and organizations. © Sila Science.
Keywords: Coaching; Decision making styles; Football; TUFAD administrators